2017
DOI: 10.1073/pnas.1610615114
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting BMP signaling input into the gene regulatory networks driving specification of the blood stem cell lineage

Abstract: Hematopoietic stem cells (HSCs) that sustain lifelong blood production are created during embryogenesis. They emerge from a specialized endothelial population, termed hemogenic endothelium (HE), located in the ventral wall of the dorsal aorta (DA). In Xenopus, we have been studying the gene regulatory networks (GRNs) required for the formation of HSCs, and critically found that the hemogenic potential is defined at an earlier time point when precursors to the DA express hematopoietic as well as endothelial gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…Success of the BMP inhibition in each case was monitored by the presence of phosphorylated SMAD‐1, 5 or 8, the downstream mediators of BMP signalling. We found that BMP input is required at three points during the development of the HSCs: firstly, for the initial expression of GATA‐2 in the DLP/DHs, later for the expression of KDR/FLK‐1 required for the response to VEGF‐A signalling, and thirdly for the expression of GATA‐2 in the DA …”
Section: The Gene Regulatory Network Controlling Definitive Haemangiomentioning
confidence: 92%
See 3 more Smart Citations
“…Success of the BMP inhibition in each case was monitored by the presence of phosphorylated SMAD‐1, 5 or 8, the downstream mediators of BMP signalling. We found that BMP input is required at three points during the development of the HSCs: firstly, for the initial expression of GATA‐2 in the DLP/DHs, later for the expression of KDR/FLK‐1 required for the response to VEGF‐A signalling, and thirdly for the expression of GATA‐2 in the DA …”
Section: The Gene Regulatory Network Controlling Definitive Haemangiomentioning
confidence: 92%
“…However, BMP is required for the whole of lateral plate mesoderm formation and general patterning of the early embryo. Therefore, to test the specific role around the time when GATA‐2 expression was turned on in the DLP/DHs, we had to make use of conditional inhibition of BMP signalling . We therefore obtained a transgenic Xenopus line expressing the BMP inhibitor, Noggin, from a heat shock‐inducible promoter, and separately a chemical inhibitor of BMP signalling that could be added to the water housing the experimental embryos.…”
Section: The Gene Regulatory Network Controlling Definitive Haemangiomentioning
confidence: 99%
See 2 more Smart Citations
“…One thing that is clear from the papers that follow is that the impact of thinking on gene networks in bioscience is truly broad and deep. The topics span a wide range, from the differentiation of germ cells (1), immunology (2,3), and the molecular basis of celltype differentiation (4)(5)(6)(7)(8)(9)(10)(11), to paleontology (12,13) and behavior (14). The central role of network thinking is revealed in the way it allows for both the design of testable experimental frameworks to probe complex biological processes and the conceptual framework for understanding biological mechanisms.…”
mentioning
confidence: 99%